2003
DOI: 10.3168/jds.s0022-0302(03)73893-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nutritive Utilization of Protein and Magnesium in Rats with Resection of the Distal Small Intestine. Beneficial Effect of Goat Milk

Abstract: The search for diets to improve the nutritive utilization of protein and magnesium in malabsorption syndrome led us to study goat milk, because of its particular nutritional characteristics, and to compare it with cow milk, which is most commonly consumed. We studied the nutritive utilization of protein and magnesium in transected rats (control) and in rats with resection of 50% of the distal small intestine. The diets used were the standard diet recommended by the American Institute of Nutrition and diets bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 17 publications
4
38
0
4
Order By: Relevance
“…Notably, their nutritional value of component flavored goat cheese, but also for its sensory acceptability for children foods. This is agreed by [27] the consumption of goat milk produces a better protein efficiency ratio and food conversion efficiency values, particularly in rats with intestinal resection, together with a higher nutritive utilization of protein. pH value is indirectly affected in the microstructure and texture as well as sensory evaluation of cheese.…”
Section: Discussionsupporting
confidence: 52%
“…Notably, their nutritional value of component flavored goat cheese, but also for its sensory acceptability for children foods. This is agreed by [27] the consumption of goat milk produces a better protein efficiency ratio and food conversion efficiency values, particularly in rats with intestinal resection, together with a higher nutritive utilization of protein. pH value is indirectly affected in the microstructure and texture as well as sensory evaluation of cheese.…”
Section: Discussionsupporting
confidence: 52%
“…Flavour of milk samples enriched with lavender and mint was significantly different (p<0.05) from flavour of other enriched goat's milk samples. However, due to the highest bitterness and astringency of lavender extract, goat's milk containing lavender was also characterized by the highest intensity of these properties and thus conse- (1)(2)(3)(4)(5) for each attribute multiplied with an importance factor (IF) determined for each attribute (IF=2 for flavour, overall acceptability and aroma familiarity, IF=1.5 for sweetness, IF=1 for bitterness and astringency and IF=0.5 for colour). LB= lemon balm, M=mint, L=lavender, R=rosemary, S=sage, GM=plain goat's milk, GM+LB=GM enriched with lemon balm extract, GM+M=GM enriched with mint extract, GM+L=GM enriched with lavender extract, GM+R=GM enriched with rosemary extract, GM+S=GM enriched with sage extract quently low overall acceptability.…”
Section: Sensory Properties Of Plant Extracts and Formulated Enrichedmentioning
confidence: 99%
“…During past years, goat's milk has received increasing attention due to its specific, but highly valuable nutritive composition, biological and therapeutic values. Improved digestibility, higher mineral composition quality, buffering capacity, higher therapeutic efficiency and many other characteristics are significantly differing goat's milk from other milk types (5). Today goat's milk is regarded as a high-quality raw material used for production of food for infants and the elderly, for population with certain medical problems, as well as for production of a wide range of other food products, including beverages (low fat, fortified, or flavoured) and UHT (ultra high temperature) milk, fermented products (cheese, buttermilk or yogurt), frozen products (ice cream or frozen yogurt), but also butter, condensed/dried products, sweets and candies (6).…”
Section: Introductionmentioning
confidence: 99%
“…López-Aliaga et al [43] reported that the magnesium apparent digestibility coefficient was greater when goat milk was included in the diet of rats with resection of the distal small intestine, this effect being reflected in the greater quantity of this mineral stored in bone (femur and sternum). With respect to the levels of magnesium in the blood, the animals given the goat milk diet presented a higher quantity of magnesium in the erythrocytes, due to its greater digestive utilization.…”
Section: Magnesiummentioning
confidence: 99%
“…López-Aliaga et al [43] investigated the effect of dietary goat milk on the nutritive utilization of protein in rats with resection of 50% of the distal small intestine. They reported that goat milk consumption led to a better protein efficiency ratio and food conversion efficiency together with a higher digestibility of protein and high values of nitrogen balance values in comparison with cow milk, particularly in rats with distal small intestine resection.…”
Section: Effects Of the Consumption Of Goat Milk On The Nutritive Utimentioning
confidence: 99%